STAT3 inhibitor WP1066 as a novel therapeutic agent for renal cell carcinoma - Horiguchi, A (Nature Publishing Group, 2010)
BACKGROUND: Signal transducer and activator of transcription 3 (STAT3) regulates the expression of genes that mediate cell survival, proliferation, and angiogenesis and is aberrantly activated in various types of malignancies, including renal cell carcinoma (RCC). We examined whether it could be a novel therapeutic target for RCC by using the STAT3 inhibitor WP1066. METHODS: The antitumour activities and related mechanisms of WP1066 were investigated in vitro on renal cancer cell lines and in vivo on murine xenografts. RESULTS: In Caki-1 and 786-O renal cancer cells, 5 μM WP1066 prevented the phosphorylation of STAT3, and 2.5 μM WP1066 significantly (P<0.01) inhibited cell survival and proliferation. WP1066 suppressed the expression of Bcl-2, induced apoptosis, and inhibited the basal and hypoxia-induced expression of HIF1α and HIF2α, as well as vascular endothelial growth factor secretion into cell culture medium. Human umbilical vascular endothelial cells cocultured with media from WP1066-treated cells showed significantly reduced tubulogenesis (P<0.05). Systemic oral administration of WP1066 to mice for 19 days significantly inhibited the growth of Caki-1 xenograft tumours (P<0.05), and pathological analysis of xenografts of WP1066-treated mice showed decreased immunostaining of phosphorylated STAT3 and reduced length of CD34-positive vessels (P<0.05). CONCLUSION: Our results suggest that using WP1066 to inhibit the STAT3 signalling pathway could be a novel therapeutic strategy against RCC.